Police Matters : c y Radha Kumar. - Kumar, Radha, 1981-; Project Muse. (Ithaca [New York] : Cornell University Press, 2021)
"A history of the entwinement of everyday police and caste authority in the colonial and postcolonial Tamil countryside in twentieth-century south India"--
State Knowledge : Seeing Like a Policeman -- Police Documents : The Politics of "False Cases" -- Routine Coercion : Scarred Bodies, Clean Records -- "Unlawful Assembly" in Colonial Madras -- Illegitimate Force in Postcolonial Politics.
Description based on print version record.
Keywords: Police-community relations; Police; Law enforcement; Caste -- Political aspects; Caste-based discrimination; Caste-based discrimination -- India -- Tamil Nadu -- History -- 20th century; Police-community relations -- India -- Tamil Nadu -- History -- 20th century; Caste -- Political aspects -- India -- Tamil Nadu -- History; Law enforcement -- India -- Tamil Nadu -- History -- 20th century; Police -- India -- Tamil Nadu -- History -- 20th century; India -- Tamil Nadu; History; Electronic books